Effects of soil type and composition of rhizodeposits on rhizosphere priming phenomena - Lloyd, Davidson A.; Ritz, Karl; Paterson, Eric; Kirk, Guy J.D. (Elsevier, 2016)
Inputs of fresh plant-derived C may stimulate microbially-mediated turnover of soil organic matter (SOM) in the rhizosphere. But studies of such ‘priming’ effects in artificial systems often produce conflicting results, depending on such variables as rates of substrate addition, substrate composition, whether pure compounds or mixtures of substrates are used, and whether the addition is pulsed or continuous. Studies in planted systems are less common, but also produce apparently conflicting results, and the mechanisms of these effects are poorly understood.